Financial Distress, What Factors Affect It? - Anggraeni, Titi; Hady, Hamdy; Nalurita, Febria (Gema Wiralodra, 2024)
Every company, small or large, can experience financial distress, to anticipate it, company need to know the factors that lead to financial distress. This study aimed to examine the relationship between operation cash flow, leverage, size of the company, retained earnings, director size, and audit committee on financial distress. This study used 114 manufacturing companies listed on the Indonesian stock market from the year 2018 until 2022. This research added director size and audit committee. The research uses quantitative data, and the data type used is secondary data collected from the financial reports of the companies under study listed on the Indonesia Stock Exchange. The result showed that operation cash flow, size of company, retained earnings, and director size have negative relationships with financial distress. However, leverage and audit committees have positive relationships. Management needs to manage operating cash flow, minimize leverage, manage the size of the company and retained earnings also manage the size of the director and audit committee according to the size of the company.